PENGARUH STRATEGI GENIUS LEARNING DISERTAI METODE PENEMUAN TERBIMBING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS IX SMPN 20 PADANG TAHUN PELAJARAN 2012/2013 - Nurhamidah, Nurhamidah; Putra, Atus Amadi; Harisman, Yulyanti (Pendidikan Matematika, 2013)
The centre of learning process by the teachers and lack of motivation to find mathematic concept causes the comprehension math concept of students relatively low is the basic to do this research. The purpose of this research is to know weather the comprehension of math concept by using the Genius Learning strategy with Penemuan Terbimbing method is better than comprehension of math concept by using conventional learning at class IX of state Junior High School 20 Padang TP 2012/2013. This research is experimental research and use random sampling. To analyze the data this research used Mann-Whitney test with Minitab software. The result of hypotesis test is probability = 0,0039 with a = 0,05, so the hypotesis was accepted. So that it concludes that the comprehension of students math concept by using Genius Learning strategy with Penemuan Terbimbing method is better than comprehension of math concept by using conventional learning.